Arresting (non) citizenship: the policing migration nexus of nationality, race and criminalization - Parmar, A (SAGE Publications, 2019)
In this article I examine ‘Operation Nexus’, a collaborative initiative between the police and immigration enforcement in the UK, and its impact on foreign national and minority ethnic suspects of offending. I explain how strategic policing aims to manage migration around notions such as ‘high harm’ offenders, target those who appear ‘foreign’ as well as visible ethnic minority suspects, the latter of which may hold citizenship in the UK. The consequences of Operation Nexus are therefore wider than its stated aim because it legitimizes racial profiling by the police and has negative consequences on notions of belonging for racialized foreign nationals and citizens albeit in different ways. By presenting empirical research with those who implement Operation Nexus as well as those who experience it, I elucidate how the policing of migration revives and extends colonial premises that connect nationality, race and criminalization within the expanding and merging realm of contemporary criminal justice and migration control. I draw on Lerman and Weaver’s thesis that when contemporary criminal justice policies disproportionately affect racial and ethnic minorities, they create an unequal group of people that are exiled within their own society and disenfranchised from public institutions such as the police.